Thermal wear behaviour of H13 tool steel in die casting process - Abdulhadi, Hassan Abdulrssoul (2017)
During die casting, tools for die casting and hot forging applications are subjected to thermal cycles, which may induce high stress that always lead to plastic deformation. The interaction behaviour of these materials with the thermal and mechanical conditions are necessary to be studied through experimental and numerical simulation studies. The optimization of the samples thermo-mechanical conditions have formed the basis of several scientific studies. This study examined the thermal wear behaviour of A1S1 H13 steel, a conventional aluminum alloy die casting material when subjected to cyclic heating and cooling cycles. The experimental and simulation studies were effectively controlled via a thermal wear system that ensured a minimum heat loss from the furnace during the casting process. The quenching system provided a continuous water flow of 32 °C. Cylindrical samples of diameter 33 mm and wall thickness 6.5 mm were used. The samples were subjected to alternating heating (dipping in aluminum alloy at 700 °C) and cooling (at room temperature) cycles of 24 s intervals each. The die surface initiation and crack propagation were stimulated by thermal and hardness gradients acting on the contact surface layer. The effect of the machined surface roughness and die casting parameters on the thermal wear properties were studied via a developed design of experiment (DoE), while a FEM-based thermal simulation model was used for surface temperature generation and stress distribution at the studied temperatures. The experimental data were assessed on a thermo-mechanical wear life assessment model, assisted by response surface methodology (RSM). The testing was successively done at 1,850, 3,000, and 5,000 cycles. After each number of cycles, all the sample surfaces were visually inspected. The thermally-worn samples were characterized for metallographic, surface crack, and hardness characteristics. The samples were later segmented and analyzed through optical and scanning electron microscopy (SEM). Additionally, Energy Dispersive X-ray Spectroscopy (EDXS) was performed on the areas surrounding the cracks. The maximum crack length and Vickers hardness profile of the thermal wear cracks were obtained. The results of the metallographic and morphological studies indicate an increase in surface crack formation with an increasing number of cycles, suggesting an increase in thermal stresses at higher number of cycles. The crack length of the spherically-ended Region I was about 47 to 127 μm. Meanwhile, a high oxygen content was observed within 140 μm distances from the sample surface, which led to oxidation. At 700 ˚C, aluminum oxides formed and in contact with the H13 sample surface. These stresses propagate the thermal wear crack length into the tool material of differently-shaped Region I and cylindrically-shaped Region II, while a different case was observed for the hardness. The crack length of Region I was about 32 % higher than that of Region II, while a different case was observed for the hardness. Based on the model, the best results were achieved at an optimal condition of crack length 26.5 μm, surface roughness 31.14 μm and hardness property 306 HV0.5; showing that the RSM effectively related the wall thickness, machine surface roughness, and immersion time to the responses. The variation between the experimental and predicted simulation data was less than 5 %, showing the validity of the model. In conclusion, an effective experimental and simulation system for the determination of the thermal wear and surface failure of die materials in real die-casting environments was developed and validated. Similarly, the relationship between the machined surface roughness, wall thickness, and immersion time of the AISI H13 tool with its thermal wear formation was established.